LIMBAH FLY ASH PABRIK MINYAK NABATI SEBAGAI BAHAN SUBSTITUSI SEMEN DALAM PEMBUATAN BATAKO - Doly P Silaban; Alexius Luther Ola (Balai Riset Dan Standardisasi Industri Manado, 2019)
Utilization of fly ash waste to subtitute portland cement in concrete brick fabrication to resolve enviromental problem has been done. This research used fly ash from waste of vegetable oil industry at Bitung City. Descriptive method has been used to interprete data with sand and fly ash composition as free variable and portland cement composition as constant variable. At the beginning As, Cd, Cr, Hg and Pb concentration in fly ash was analyzed and comply minimum standard on Indonesia government regulation (PP No 18 Tahun 1999) about dangerous waste, so it could be used as concrete bricks raw materials. Sample prototype dimension was molded in (cm) 27x12x8 with 10 samples for one test and data was provided from two repetition. Compressive Strength from fly ash mixing showed value (kg/cm2) 27.77-64.22 with water absorption value (%) 9.62-16.79. Compressive strength value of concrete brick from fly ash mix comply SNI 03-0349-1989 standard on grade III and IV.